Autochthonous Hepatozoon infection in hunting dogs and foxes from the Czech Republic - Mitková, Barbora; Hrazdilová, Kristýna; Steinbauer, Vladimír; D'Amico, Gianluca; Mihalca, Andrei Daniel; Modrý, David (Parasitology research, 2016)
Blood samples from 21 red foxes (Vulpes vulpes) and 8 hunting dogs from the same locality in the Czech Republic were examined for presence of Hepatozoon canis/Hepatozoon sp. The dogs were selected based on their close contact with foxes during fox bolting and because they had not traveled into known endemic areas. Using diagnostic PCR amplifying partial 18S rDNA fragment, Hepatozoon DNA was detected in 20 red foxes (95 %) and 4 dogs (50 %). From 8 positive foxes and 2 positive dogs, we obtained nearly complete 18S rDNA sequences. Phylogenetic analyses of these sequences revealed very low variability. Buffy coat smears from positive dogs were prepared and examined. No Hepatozoon gamonts were found. This study provides the first report of autochthonous infection of H. canis/Hepatozoon in dogs and foxes from the Czech Republic. Our study indirectly demonstrates cross infection between red foxes and dogs and confirms autochthonous infection of Hepatozoon canis in dogs living in a geographic area well outside the range of Rhipicephalus sanguineus sensu lato, which is so far the only known vector of H. canis in Europe.
Keywords: Animals; Eucoccidiida; ribozomální DNA; Female; DNA, Ribosomal; arachnida jako vektory; ženské pohlaví; nemoci psů; lišky; Dog Diseases; kokcidióza; Dogs; Coccidiosis; Phylogeny; Male; Foxes; Czech Republic; Sequence Alignment; Sequence Analysis, DNA; Česká republika; zvířata; mužské pohlaví; sekvenční analýza DNA; Arachnid Vectors; fylogeneze; psi; sekvenční seřazení; Rhipicephalus sanguineus